Internet Marketing Development In Malaysia -- A Study Of Malaysian Marketing Managers' Perceptions - Teh, Ya Yee (2008)
This researched focused on public listed companies in Malaysia, to investigate their marketing manager's perceived impact of the Internet towards the company marketing function.